Global seasonal urban, industrial, and background NO2 estimated from TROPOMI satellite observations - V. Fioletov; C. A. McLinden; D. Griffin; X. Zhao; H. Eskes (Atmospheric Chemistry and Physics)
The tropospheric NO2 vertical column density (VCD) values measured by the Tropospheric Monitoring Instrument (TROPOMI) were used to study the NO2 variability and estimate urban NOx emissions for 261 major cities worldwide. The used algorithm isolated three components in tropospheric NO2 data – background NO2, NO2 from urban sources, and NO2 from industrial point sources – and then each of these components was analyzed separately. The method is based on fitting satellite data by a statistical model with empirical plume dispersion functions driven by a meteorological reanalysis. Unlike other similar studies that studied plumes from emission point sources, this study included the background component as a function of the elevation in the analysis and separated urban emissions from emissions from industrial point sources. Population density and surface elevation data as well as coordinates of industrial sources were used in the analysis. The largest per capita emissions were found in the Middle East, and the smallest were in India and southern Africa. The largest background component was observed over China and parts of Europe, while the smallest was over South America, Australia, and New Zealand. Differences between workday and weekend emissions were also studied. Urban emissions on Sundays (or Fridays for some countries) are typically 20 %–50 % less than workday emissions for all regions except China. The background component typically does not show any significant differences between workdays and weekends, suggesting that background NO2 has a substantially longer lifetime compared to that in the urban and industrial plumes.